Application of Ethnoscience in Physics Education through Terasi: Theoretical and Literary Studies - Oktaffi Manasikana; Muzzazinah M; Isnanik Juni Fitriyah; Bee Koon; Paul Deuren (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2024)
This research explores the application of ethnoscience in physics education by using shrimp paste (shrimp paste) as a learning medium. Through a qualitative approach involving theoretical and literature reviews, this research illustrates how physics concepts can be taught through the traditional process of making shrimp paste and analyzes effective strategies from previous research. Data were collected from academic sources, including journals, books, and articles related to ethnoscience, physics education, and shrimp paste production. This research identifies key physics concepts in making shrimp paste, such as fermentation, chemical reactions, temperature, pressure, and diffusion, and integrates these concepts into a physics curriculum model. The literature review evaluates past research to highlight successful strategies for implementing ethnoscience in physics education. Findings show that integrating local cultural practices such as shrimp paste production increases students' understanding, motivation, and engagement by providing relevant and meaningful learning experiences. Analysis shows that contextual learning, development of critical thinking skills, and strong student-community relationships are significant benefits of this approach. This research emphasizes the importance of integrating local wisdom into science education to make learning more contextual and impactful.